CdS quantum dots sensitized TiO2 nanotubes by matrix assisted pulsed laser evaporation method. Issue 7 (15th May 2016) - Bjelajac, Andjelika; Petrovic, Rada; Socol, Gabriel; Mihailescu, Ion N.; Enculescu, Monica; Grumezescu, Valentina; Pavlovic, Vladimir; Janackovic, Djordje
Abstract: Within this study a matrix assisted pulsed laser evaporation technique was employed for deposition of CdS quantum dots onto TiO2 nanotubes. The number of laser pulses and laser fluence were varied to control the amount of CdS deposit. TiO2 nanotubes were obtained via anodization technique of sputtered Ti film on FTO glass. For CdS synthesis, dimethyl sulfoxide (DMSO) was used as a matrix of the target which absorbs radiation of KrF* laser ( λ =248 nm), then evaporates enabling the deposition of CdS quantum dots dispersed into DMSO. This study showed that the size of the CdS nanoparticles synthetized in DMSO can be controlled with microwave treatment that causes the release of S 2− ions from DMSO for creation of CdS nuclei and/or their further growth. The optimization of CdS synthesis is achieved by varying the duration of the microwave treatment and the microwave power. The obtained TiO2 photoanodes with different amounts of CdS were assembled with PbS cathodes and the polysulfide electrolyte was injected between. The influence of amount of CdS deposit and the microwave treatment of CdS on photovoltaic performance of the fabricated solar cells were analyzed under AM1.5. The results showed that microwave treatment produced a Cd(S)–DMSO complex onto CdS nanoparticles which led to a higher current density of the solar cells obtained using microwave treated CdS target. Also, the increase of CdS content by increasing the number of laser pulses provided the enhance of I–V characteristics of the solar cells.